Outreach programmes and the library usage pattern of user community in three selected secondary schools in Gombak district - Durasni binti Abdullah (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
The purpose of this study is to investigate outreach programmes and the library usage pattern of the user community in three selected secondary schools in Gombak district. The objectives of this study are, to identify the outreach programmes offered by the School Resource Centre, to investigate which outreach programs help the user community, to investigate the usage pattern of school resource center among the user community and to provide the recommendations for future library outreach programmes. This study involved pre-interview with the Library Media Teacher before the questionnaires are being formed and distributed among students and teachers in three selected secondary schools in Gombak District. The primary instrument of gathering data is in the form of self-administered questionnaire. The survey was conducted with the help of school principals. A total of five hundred and forty two (542) questionnaires was sent to the selected schools. At the end of the survey, four hundred and ninety (490) usable questionnaires were returned; giving the response rate of 90.4%. Although this study is limited to only three schools, the results of this study will provide a general overview of what is happening in the schools of the Gombak district in connection with the outreach programs, how outreach programmes can help the users and what are the School Resource Centre usage patterns. In general, the outreach programmes were conducted in schools by the School Resource Centre and noticed by the students and teachers. Most of the outreach programmes help the users to borrow books outside the School Resource Centre, to build reader interest, to increase self-confidence, to get the library services and to open mind through educational visit. The study found that most of the users use the School Resource Centre for light reading material leisurely. In general, the School Resource Centre plays an important role in schools not only to provide all the facilities for teaching and learning, but also plays an important role in continuing to foster an interest of reading among the students. Students can also use their School Resource Centre to be a place for developing their talents and abilities based on their interests through the outreach programmes handled by the school resource centre.